2018
DOI: 10.1177/1074840718773381
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Outcomes for Parents of Children With Neurodevelopmental Disabilities: A Systematic Review

Abstract: Parents of children with Neurodevelopmental Disabilities (NDDs) are at risk of sleep loss. No comprehensive systematic reviews examining parental sleep outcomes in caregivers of children with NDDs exist. A systematic search was conducted between June and August 2016 examining sleep quantity, quality, sleepiness, and fatigue outcomes of caregivers of children with NDDs. Of 7,534 citations retrieved, 33 met eligibility criteria. Most studies ( n = 27) were cross-sectional, included a range of NDDs and were of "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 84 publications
(116 reference statements)
2
13
0
Order By: Relevance
“…Recently, our laboratory focused on the association between tryptophan metabolites and neurodevelopmental disorders because of recent studies reporting that patients with neurodevelopmental disorders often have a history of fatigue, daytime tiredness, and daytime sleepiness. 30,128-130 Our previous study demonstrated that autistic symptoms were correlated with higher levels of 3-methoxy-4-hydroxyphenylglycol and lower levels of 5-hydroxyindoleacetic acid, 131 suggesting that dynamic changes in the levels of tryptophan metabolites may be associated with symptoms of neurodevelopmental disorders, including sleep disturbances and fatigue.…”
Section: Tryptophan Metabolites and Fatigue Associated With Neurodevementioning
confidence: 98%
See 1 more Smart Citation
“…Recently, our laboratory focused on the association between tryptophan metabolites and neurodevelopmental disorders because of recent studies reporting that patients with neurodevelopmental disorders often have a history of fatigue, daytime tiredness, and daytime sleepiness. 30,128-130 Our previous study demonstrated that autistic symptoms were correlated with higher levels of 3-methoxy-4-hydroxyphenylglycol and lower levels of 5-hydroxyindoleacetic acid, 131 suggesting that dynamic changes in the levels of tryptophan metabolites may be associated with symptoms of neurodevelopmental disorders, including sleep disturbances and fatigue.…”
Section: Tryptophan Metabolites and Fatigue Associated With Neurodevementioning
confidence: 98%
“…Fatigue is often observed in patients suffering from bone fracture, 9 cancer, 26 coronary heart disease, 27 stroke, 28 depression, 29 and neurodevelopmental disorders. 30 Thus, most of us experi-ence fatigue and it may delay recovery from various pathological conditions.…”
Section: Fatigue-related Brain Changesmentioning
confidence: 99%
“…Sleep quality for caregivers of children with neurodevelopmental disabilities, including CP, is poorer than caregivers of typically developing children (Micsinszki et al, 2018). Adequate sleep is fundamental for good psychological health, and therefore, for caregivers, poor sleep may result in poor psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep has important implications for every aspect of a caregiver's life, although it often has received little attention. 8 Previous research has linked poor sleep or disrupted sleep in healthy adults with elevated blood pressure, poor cardiovascular outcomes, impaired memory, and increased reports of stroke, cancer, fatigue, and higher risk of obesity. [9][10][11] While there are few studies examining sleep in caregivers of children with chronic illness, and even less in caregivers of children with T1D, researchers have found that poor sleep is a concern.…”
Section: Resultsmentioning
confidence: 99%